Simulation of thermal runaway in Li-ion batteries - Korsman, Karri (My University, 2022)
Lithium-ion batteries have gained a vast and ever-growing popularity as the choice for a high energy capacity energy storage solution. With the ever-growing use of Li-ion batteries, also comes the heightened risk of accidents involving Li-ion batteries. While Li-ion batteries provide high energy capacitance and low cost, they have a risk of entering an exothermic feedback loop called the thermal runaway phenomena. This risk is further heightened with large format energy storage, such as in electric vehicles, where a single vehicle can contain thousands of battery cells in a battery pack. This thesis gives an overview of Lithium-ion battery materials, operation principle and usage, thermal runaway, its propagation, and the risks and dangers involved. This thesis then attempts to create a simulation model for a single cell thermal runaway based on an autoclave calorimetry test, where the thermal runaway of a single cell was induced by heating the cell beyond its safe temperature limits. The results of the simulated model and the test measurements are then compared and discussed, so that the information learned can be used as a base to create more accurate and complicated simulation models for thermal runaway and to design safer electric vehicle batteries. This thesis was done at the behest of Valmet Automotive EV Power, as a part of their process to develop their simulation methodology for thermal runaway simulations.
Keywords: Thermal runaway, Lithium-ion battery, Simulation, Computational fluid dynamics